Combustion Technology Essentials of Flames and Burners - Raghavan, Vasudevan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook is intended for post-graduate students in mechanical and allied engineering disciplines. It will also be helpful to scientists and engineers working in the areas of combustion to recapitulate the fundamental and generally applied aspects of combustion. This textbook comprehensively covers the fundamental aspects of combustion. It includes physical descriptions of premixed and non-premixed flames. It provides a detailed analysis of the basic ideas and design characteristics of burners for gaseous, liquid and solid fuels. A chapter on alternative renewable fuels has also been included to bring out the need, characteristics and usage of alternative fuels. Review questions have been provided at the end of each chapter which will help the students to evaluate their understanding of the important concepts covered in that chapter. Several standard text books have been cited in the chapters and are listed towards the end, as suggested reading, to enable the readers to refer them when required. The textbook will be useful for students in mechanical, aerospace and related fields of engineering. It will also be a good resource for professionals and researchers working in the areas of combustion technology.
Introduction -- Review of Combustion Thermodynamics and Kinetics -- Review of Combustion Phenomena -- Burners for Gaseous Fuels -- Burners for Liquid Fuels -- Solid Fuel Systems -- Alternative Fuels -- Numerical Modelling of Laminar Flames.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fire prevention; Buildings$1 (BProtection.s; Engines; Cogeneration of electric power and heat; Fossil fuels; Engineering Thermodynamics, Heat and Mass Transfer; Fire Science, Hazard Control, Building Safety; Engine Technology; Fossil Fuel; Combustion